Abnormal electroencephalographic rhythms from quiet wakefulness to light sleep in Alzheimer’s disease patients with mild cognitive impairment - Salamone, Enrico Michele; Carpi, Matteo; Noce, Giuseppe; Percio, Claudio Del; Lopez, Susanna; Lizio, Roberta; Jakhar, Dharmendra; Eldellaa, Ali; Isaza, Veronica Henao; Bölükbaş, Burcu; Soricelli, Andrea; Salvatore, Marco; et al. (Clinical neurophysiology, 2025)
•ADMCI patients showed higher frontal EEG delta activity vs healthy elderly in wakefulness and light sleep.•ADMCI patients had less reduction of posterior EEG alpha activity from wakefulness to light sleep.•ADMCI patients with sleep transitions had higher wakefulness EEG delta activity. Alzheimer’s disease patients with mild cognitive impairment (ADMCI) show abnormal resting-state eyes-closed electroencephalographic (rsEEG) alpha rhythms (8–12 Hz) and may suffer from daytime sleepiness. Our exploratory study tested the hypothesis that they may present characteristic EEG rhythms from quiet wakefulness to light sleep during diurnal recordings. Datasets of 34 ADMCI and 22 matched healthy elderly (Nold) subjects were obtained from international archives. EEG recordings lasted approximately 30 min. Transitions of EEG activity from quiet wakefulness (alpha-dominant) to light sleep (theta-dominant ripples) were scored according to Hori’s vigilance stages. Cortical source activities were computed using the eLORETA software. ADMCI (t-ADMCI, N = 18) over Nold (t-Nold, N = 11) participants were characterized by greater frontal EEG delta source activities and a lesser reduction (reactivity) in the posterior alpha source activities from quiet wakefulness to ripples. Notably, EEG delta source activities during quiet wakefulness were also greater in the ADMCI group transitioning to light sleep as compared to patients without said vigilance reduction. These results suggest that ADMCI patients with a greater susceptibility to daytime sleepiness may show characteristic EEG delta and alpha rhythms in the transition from quiet vigilance to daytime sleep. Our study showed a derangement of EEG rhythms during the transition to sleep possibly specific to AD.